Placental stereology: spanning the levels from molecule to whole organ - Mayhew, Terry M. (Image analysis and stereology, 2009)
Stereology can provide hard (funcrionally-relevant) quantitative informarion at different levels of 3D structural organization. My researches have applied established methods to study organ function and developed novel methods to study subcellular localization of marker probes. We have studied whole-organ function (passive diffusion) in the human placenta and quantified various processes at tissue and subcellular levels and in normal and complicated pregnancies. Fetoplacental angiogenesis and vinous growth and maturation involve phased changes particularly around mid-gestation. Growth is associatedwith increased numbers of cells or nuclei and counts have shown thatvinous trophoblast continuously renews itself via cytotrophoblast (CT) proliferation and recruitment and syncyriotrophoblast (ST) differentiation andextrusion. Integration of these processes results in changes in total oxygen (OZ) diffusive conductance which match the growing fetal mass. Similar processes occur during development of the mouse placenta and at least some arecompromised in human pregnancies. For example: šađ in pure pre-eclampsia (PE), vinous and fetoplacental vascular volumes and surfaces are similar to those seen in uncomplicated pregnancies but reduced in pure intrauterine growth restriction (IUGR) and in PE+IUGR; šbđ trophoblast extrusion is accelerated in PE and IUGR but the latter exhibits reduced CT proliferation and this perturbed steady state leads to smaller trophoblast volumes and surfaces; šcđ Oz diffusive conductances alter in various pregnancy complications, including IUGR and PE+IUGR; šdđ fetal weight is diminished, butdiffusive transport increases, in placentas from mice exposed to urban air pollution. (Abstract truncated at 2000 characters)
Keywords: placenta; stereologija; plod; rast; morfologija